De la Guerra Fría a la crisis identitaria: la OTAN frente al aislacionismo, el imperialismo y la multipolaridad - Castelltort Claramunt, Magí (Journal of the Spanish Institute for Strategic Studies, 2025)
The strategic retrenchment of the United States, driven by its energy independence and rising public demand for domestic investments, has been mistakenly interpreted as a sign of weakness by emerging powers like Russia and China, even though Washington remains, by far, the world’s leading military power. American energy self-sufficiency bolsters its global standing by reducing dependence on the Middle East and constraining Moscow’s ability to secure funding. In light of growing public pressure to cut military expenditures, NATO will need to assume greater responsibility for European defense, sharing burdens and facilitating the U.S. pivot to Asia, while avoiding any expansion beyond the Atlantic region or its military mandate. The Alliance must legitimize itself in the eyes of citizens not only as a defender of territorial integrity and democratic principles but also as a cornerstone of the welfare state.
Keywords: U.S. retrenchment; energy sovereignty; Russian revisionism; demilitarization